PENGARUH PEMANFAATAN SENSOR PROXIMITY TERHADAP VOLUME PENGGUNAAN CAIRAN BILIK DISINFEKTAN SEMI-OTOMATIS - S N Mustika; S. Sendari; Y. Rahmawati; Y.D. Mahandi; F.I. Avinda; M.A. Rosyadi; G.A. Putra; F.A. Finzaqi; F. Daniswara; M.C. Bagaskoro; A.D. Fachriyyah; D.M.A. Sari; M.H. Rizqullah; R.K. Putra (Buletin Udayana Mengabdi, 2020)
The Covid-19 pandemic is a disease caused by a virus, namely Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and has become a global problem. The spread of this virus can be said to be very easy and fast because it can only be through interaction. According to WHO, the spread of the corona virus can be through several things such as droplets, air, contaminated surface objects, and fecal-oral or human waste. Several efforts have been called for as prevention and breaking the covid-19 chain. One of them is spraying disinfectant liquid to remove or kill microorganisms, including the type of corona virus. However, on the other hand, the use or spray of disinfectant liquid directly on humans has a risk, especially on the face, which is a sensitive part. With the semi-automatic disinfectant booth equipped with a height detector, it is an alternative to reduce this risk and use fluids as needed.